IMPLEMENTASI KONSEP PENDIDIKAN KARAKTER KI HAJAR DEWANTARA DI SMP NEGERI 2 BOJONEGORO - Fauziatun Nisa’, Ida; Miftah, Zaini (At-Tuhfah : Jurnal Studi Keislaman, 2021)
in this increasingly modern and growing age, especially in technological systems Communication and information, and the mindset of age children grows Adolescence or puberty. To compensate for it all so that the child will not be distracted by it Technological advances are more sophisticated, and children's character education needs attention, Whether in the family circle, school, or community. This research is meant to know Ki Hajar Dewantara character education concepts and implementation in public junior high school 2 "Bojonegoro. The study uses qualitative deskriptive methods. The data collection techniques used are observations, interviews, book collections ki dewantara, and Documentation. As for the results of this study, (1) the educational concept of character ki Dewantara includes, ki dewantara vision, basic character education, principles of Education, three education centre, among system, Tri Sakti Jiwa, Tri-naga concept (Ngerti, Ngroso, Nglakoni), Tri-kon concept, (Kontinu, Konvergen, Konsentri). (2) implementation of education concepts Ki hajar dewantara in public junior high school 2 Bojonegoro by using breeding positive activity of teachers, students, and the entire community at school. Because of the covid-19 pandemic condition has diverted both learning and character education at home each with his parents as his education. Teachers teach parents how to train good children and always communicate through the whatsapp guardian santri group. In addition, students are scheduled with a limited amount to learn hydroponics and to learn gamelan directly at school. This is done to alleviate a child's long-term exposure to online learning. Assessments and character education conducted at public school 2 Bojonegoro by paying regular visits each day, private conversations, and conversations to parents. In addition to coordination meetings every month and year.